Impact of educational intervention on knowledge and attitude of bio-medical waste management among health care personnel working in a tertiary care hospital of Bengaluru city, Karnataka, India - Sharma, Nidhi; Hiremath, Lalita D.; D., Sudeepa; H. V., Kiran Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: The waste produced in the course of healthcare activities carries a higher potential for infection and injury than any other type of waste. Inadequate and inappropriate knowledge of handling of healthcare waste among health care personnel may have serious health consequences and a significant impact on the environment as well. Hence this study was undertaken to assess the knowledge and attitude regarding the bio-medical waste management among nurses and laboratory technicians working in our hospital and to evaluate the effect of the intervention program given to them. Methods: A quasi-experimental study was conducted among the nurses and laboratory technicians working at The Oxford Medical College, Hospital and Research Centre, Bengaluru. An identical pre-designed and pre-tested structured questionnaire was given to them before and after the training session. Results: After the training program, a statistically significant increase in knowledge on all aspects of bio-medical waste management was found among the study participants. The attitude on all aspects related to BMW management improved among the participants after the intervention. Conclusions:All health care personnel must undergo regular training in BMW management. This should be coupled with effective implementation of rules and regular monitoring by authorities.